PERENCANAAN BANGUNAN PEMECAH GELOMBANG (BREAKWATER) TIPE GROIN DENGAN BAHAN TETRAPOD DI PANTAI JASRI , KABUPATEN KARANGASEM - I Gede Agus Widhiana Putra; Putu Eryani (Program Studi Teknik Sipil, Fakultas Teknik dan Perencanaan, Universitas Warmadewa, 2018)
Karangasem Regency has a beach length of 71 Km with several conditions of coastal sedimentary material. In recent years the beach in Karangasem has experienced erosion and setback of coastline, one of which is Jasri Beach. Handling for this coastal segment has been carried out several times by Karangasem Regency, but still has construction failure. This condition certainly causes 2 consequences because, among other things, the type and dimensions of the building are not in accordance with the characteristics of the study area, the handling concept presented is not in accordance with the requirements. Therefore, it is necessary to handle such as coastal safeguards and breakwaters.. Where in this journal selected Groin type breakwater buildings that function to hold sediment transfor along the coast, so as to reduce / stop erosion that occurs.